ANALISIS VALIDITAS LEMBAR KERJA SISWA (LKS) BERBASIS COLLABORATIVE CREATIVITY POKOK BAHASAN RANGKAIAN ARUS SEARAH PADA SISWA SMAN PAKUSARI - Novia Nur Widia; Trapsilo Prihandono; Singgih Bektiarso (FKIP Universitas Jember, 2019)
This research aimed to describe and analyzed the validity of Student Worksheet (LKS) based on Collaborative Creativity on the subject of direct current circuits on high school students. The type of this research in educational development research. This study used research and development prosedures according to Nievenn (2006). Validation was done by expert validators and user validators. The technique of collecting data used a validation sheet of the student worksheet developed. Based on the result of the validation of the user validators was 4,32 which was include in the valid category and the result oh the expert validator was 4,05 which fall in to the valid category. Students Worksheets which was developed can increase students learning outcomes by gaining 0,7189 and high category. Thus, Collaborative Creativity based Student Worksheet (LKS) based on direct current circuits was include in the valid category and feasible category used as students worksheet in direct current material learning for class XII science.Keywords : Validity, Students Worksheet, Collaborative Creativity